The Inventory of Large Carnivores and Conflict Avoidance Measures from Natura 2000 Cold Someş - Marian PROOROCU; Cristina Maria AVRAM; Maria TUPIŢĂ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2020)
The main measures for the protection and conservation of large mammals are: the avoidance of illegal logging and thisings leading to fragmentation and even the disappearance of habitats, rational management of the trophic base represented by wild herbivores, in the case of large carnivores, elimination/reduction of poaching and control of hunting activities, etc.